Heart Rate Reserve in Fontan Patients: Chronotropic Incompetence or Hemodynamic Limitation?. Issue 9 (7th May 2019) - Claessen, Guido; La Gerche, Andre; Van De Bruaene, Alexander; Claeys, Mathias; Willems, Rik; Dymarkowski, Steven; Bogaert, Jan; Claus, Piet; Budts, Werner; Heidbuchel, Hein; Gewillig, Marc
Abstract : Background: Patients with a Fontan circulation achieve lower peak heart rates (HR) during exercise. Whether this impaired chronotropic response reflects pathology of the sinoatrial node or is a consequence of altered cardiac hemodynamics is uncertain. We evaluated the adequacy of HR acceleration throughout exercise relative to metabolic demand and cardiac output in patients with a Fontan circulation relative to healthy controls. Methods and Results: Thirty subjects (20 healthy controls and 10 Fontan patients) underwent cardiac magnetic resonance imaging with simultaneous invasive pressure recording via a pulmonary and radial artery catheter during supine bicycle exercise to near maximal exertion. Adequacy of cardiac index, stroke volume, and HR reserve was assessed by determining the exercise‐induced increase (∆) in cardiac index, stroke volume, and HR relative to the increase in oxygen consumption (VO2 ). HR reserve was lower in Fontan patients compared with controls (71±21 versus 92±15 bpm; P =0.001). In contrast, increases in HR relative to workload and VO2 were higher than in controls. The change in cardiac index relative to the change in VO2 (∆cardiac index/∆VO2 ) was similar between groups, but Fontan patients had increased ∆HR/∆VO2 and reduced ∆ stroke volume/∆VO2 compared with controls. There was an early and marked reduction in stroke volume during exercise in Fontan patients corresponding with a plateau in cardiac output at a low peak HR. Conclusions: In Fontan patients, the chronotropic response is appropriate relative to exercise intensity, implying normal sinoatrial function. However, premature reductions in ventricular filling and stroke volume cause an early plateau in cardiac output beyond which further increases in HR would be physiologically implausible. Thus, abnormal cardiac filling rather than sinoatrial node dysfunction explains the diminished HR reserve in Fontan patients.